Effect of Pyrolysis Temperature on Electrochemical Performance of SU-8 Photoresist Derived Carbon Films. (7th August 2015) - Kakunuri, Manohar; Sharma, Chandra Shekhar
Abstract : In this paper, we analyze the effect of pyrolysis temperature on the structural and electrochemical properties of SU-8 photoresist derived carbon films fabricated on stainless steel wafer substrate. Pyrolysis was done in two step in the presence of nitrogen at different temperatures from 973 to 1273 K. X-ray diffraction, small angle X-ray scattering and Raman spectroscopy techniques were used to characterize the microstructure of these carbon films. Additionally, carbon and hydrogen content of carbon films were also analyzed using elemental analyzer. Further electrochemical characteristics of as prepared binder free carbon films were investigated using galvanostat charge/discharge experiments, electrochemical impedance spectroscopy and cyclic voltammetry. Results were then correlated with the microstructural changes in the carbon films prepared at different pyrolysis temperature.